2012
DOI: 10.1152/jn.00002.2012
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to heading direction dissociates the roles of human MST and V6 in the processing of optic flow

Abstract: The extraction of optic flow cues is fundamental for successful locomotion. During forward motion, the focus of expansion (FoE), in conjunction with knowledge of eye position, indicates the direction in which the individual is heading. Therefore, it is expected that cortical brain regions that are involved in the estimation of heading will be sensitive to this feature. To characterize cortical sensitivity to the location of the FoE or, more generally, the center of flow (CoF) during visually simulated self-mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 63 publications
5
38
0
Order By: Relevance
“…However, using functional MRI, Cardin et al (2012) suggest that only MST is implicated in the extraction of optic flow for computation of heading direction. While MST might provide a representation of heading perception, V6 would rather be concerned with obstacle avoidance during self-motion as inferred by Cardin et al (2012).…”
Section: Is the Temporal Cortex Involved In A Velocity Pathway?mentioning
confidence: 99%
“…However, using functional MRI, Cardin et al (2012) suggest that only MST is implicated in the extraction of optic flow for computation of heading direction. While MST might provide a representation of heading perception, V6 would rather be concerned with obstacle avoidance during self-motion as inferred by Cardin et al (2012).…”
Section: Is the Temporal Cortex Involved In A Velocity Pathway?mentioning
confidence: 99%
“…Interestingly, despite the V6 preference for self-motion over other types of global motion, a recent study surprisingly suggests that V6 does not encode direction of heading (Cardin et al, 2012). Given that disparity is most informative for nearby objects that generate relatively large retinal disparities, the authors suggested that V6 may be concerned with flow for the purpose of avoiding obstacles during self-motion rather than for providing a representation of heading direction (Cardin et al, 2012).…”
Section: Area V6 In the Human Brainmentioning
confidence: 99%
“…Given that disparity is most informative for nearby objects that generate relatively large retinal disparities, the authors suggested that V6 may be concerned with flow for the purpose of avoiding obstacles during self-motion rather than for providing a representation of heading direction (Cardin et al, 2012). The selective preference of V6 for the 3D translational egomotion shown in Sdoia et al (2009) lends support to this view.…”
Section: Area V6 In the Human Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, activations resulting from ipsilateral visual motion stimulation in fMRI experiments have been attributed to hMST assuming that basic neuronal properties would have been preserved across species. Further imaging studies have revealed that hMST indeed resembles its monkey homolog in many important aspects, such as the preference for coherent motion as compared with motion noise (Becker et al, 2008;Fischer et al, 2012;Helfrich et al, 2013) or the selectivity for specific optic flow structures (Wall et al, 2008;Cardin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%